Asymmetric information about volatility and option markets - Saikat Nandi (Federal Reserve Bank of Atlanta, 1995)
This paper develops a model of asymmetric information in which an investor has information regarding the future volatility of the price process of an asset but not the future asset price. It is shown that there exists an equilibrium in which the investor trades an option on the asset and expressions for the equilibrium option price and the dynamic trading strategy of the investor are derived endogenously. It is found that the expected volatility of the underlying asset increases in the net order flow in the option market. Also, the depth of the option market is smaller when there is more uncertainty about the variance of the underlying asset, which is conceptually consistent with empirical findings in the equity option market.
Keywords: 330; Options (Finance); Financial markets